Pengaruh Lama Perendaman dari Berbagai Zat Pengatur Tumbuh Alami Terhadap Pertumbuhan Stek Batang Tanaman Jeruk Nipis (Citrus aurantifolia S.) - Syahrul Arifin (JURNAL MAHASISWA AGROTEKNOLOGI (JMATEK), 2020)
The design used in this research is the design of random Group (RAK) Facoryl with 2 factors, thefirst factor of organic zpt (Z) with 4 levels namely: Z0 (control), Z1 (red onion extract), Z2 ( extractbamboo shoots), Z3 ( extract coconut water). Long immersion (P) with 3 levels, i.e. P1 (2 hours), p2(4 hours), p3 (6 hours). There are 12 combinations of treatments that are repeated 3 times resultingin 36 units of trial. The test result Data is analyzed by using the analysis of Variant (ANOVA) andcontinued with real difference test honestly (BNJ). The parameters observed in this study were:height buds, number of shoots, number of leaves and the length of the roots. The results showed that the administration of ZPT organic and long immersion gave a noticeable effect on all parameters. Intraction treatment gives a noticeable effect on the length of the parameters of the roots on observation 8 weeks after planting.